A fuzzy logic approach for detecting redirection spam. (2016) - Hans, Kanchan; Ahuja, Laxmi; Muttoo, S.K.
Redirection spam is a relatively newer technique whereby spammers redirect the search user to an unwanted webpage or download malware on the victim's machine without his consent. Spammers are making use of chained redirections to hide their nefarious activities. Detecting such malicious redirections is of prime importance for maintaining web security. In this paper, we have identified the factors that assist in detecting redirection spam and propose a fuzzy logic-based model for redirection spam detection. We validated our model against a set of URLs and were able to detect the spammed redirections with high accuracy.